FORMULATION AND EVALUATION OF MOUTH-DISSOLVING ORAL FILM OF NICOTINE USING QUALITY BY DESIGN APPROACH - PAWAR, SACHIN DATTRAM; SHINDE, NAGOJI; RAVI, GUNDAWAR; KALYANKAR, TUKARAM (International Journal of Applied Pharmaceutics, 2025)
Objective: Nicotine is a natural alkaloid found in Nicotiana tabacum and is widely used as a potent stimulant. This study aims to extract and characterize nicotine from tobacco powder and formulate a nicotine-containing Oral Fast-Dissolving Film (OFDF) for nicotine replacement therapy. Methods: Nicotine was extracted from tobacco using water and Hydrochloric Acid (HCL). Purification was performed using column chromatography. The extracted nicotine was characterized using UV-visible spectroscopy, XRD, SEM, and FTIR. The OFDF was prepared using a Quality by Design (QbD) approach; a factorial design 3x3 was employed for film optimization. The solvent casting method was used for film preparation. The optimized formulation was evaluated for folding endurance, disintegration time, and drug release. Stability studies were performed as per ICH guidelines. Results: The extraction process successfully yielded purified nicotine in crystalline form, having a crystalline index of 88.89%. The extracted nicotine shows lambda max at 260 nm; the FTIR study confirms the stretching and bending vibration frequencies for nicotine. The polymer Hydroxypropyl Methylcellulose (HPMC-E5) and plasticizer Polyethylene Glycol (PEG) concentrations (w/w) were selected as independent variables. At the same time, disintegration time, folding endurance, and dissolution time were evaluated as dependent variables for QbD. All the formulations were assessed, and FF3 is the optimized batch based on the dissolution, drug content, and folding endurance. Conclusion: Nicotine was extracted and purified. The purified nicotine was then incorporated into an OFDF, which exhibited rapid disintegration and dissolution. This formulation can aid patients experiencing nicotine withdrawal symptoms by providing a safer, immediate nicotine release.